Je preskripce pohybové aktivity soucásti lécebne-preventivní péce civilizacních chorob? Výsledky dotazníkového setrení lékarů - Dad'ová, K; Radvanský, J; Pelísková, P; Slabý, K; Smítková, H; Mácková, J (Casopis lekaru ceskych, 2007)
BACKGROUND: Low level of physical activity is an independent risk factor of civilization disorders. Intervention for increasing physical activity has been for generations mentioned in health care. Because of low adherence of the population to those general appeals it is necessary to improve radically the knowledge of health professionals about individual exercise prescription. The aim of this study was to analyze approach of medical doctors in this particular dilemma. METHODS AND RESULTS: A questionnaire was distributed at postgraduate courses for medical doctors. Data from doctors of different specializations were summarized (N=657, from which 458 were females, i.e. 69,7 %, mean age=38,8+/-9,74). 96,4 % of doctors stated that they recommend exercise to their patients though only up to 23,4 % of them are regularly asked by their patients about the exercise. Concrete (type, intensity, duration and frequency) or individually tailored recommendation give 66,2 %, or 62,6 % of doctors respectively. Most respondents (56,0 %) also recommend a consultation of another specialist (mostly rehabilitation doctor and physiotherapist). Majority of addressed professionals shows that current medical education structure does not enable adequate prescription of physical activity without the help of specialist. CONCLUSIONS: Study showed a positive attitude of medical doctors to exercise prescription. However, information about the need of individualized prescription and knowledge about possibilities of exercise therapy in particular regions should be increased.
Keywords: Prescriptions; postoj zdravotnického personálu; podpora zdraví; dospělí; lékařské předpisy; Adult; tělesná výkonnost; Exercise; Humans; Physicians; Attitude of Health Personnel; cvičení; lidé; lidé středního věku; lékaři; Middle Aged; Physical Fitness; Health Promotion